Burkitt lymphoma beyond MYC translocation: N-MYC and DNA methyltransferases dysregulation. Issue 1 (December 2015) - De Falco, Giulia; Ambrosio, Maria; Fuligni, Fabio; Onnis, Anna; Bellan, Cristiana; Rocca, Bruno; Navari, Mohsen; Etebari, Maryam; Mundo, Lucia; Gazaneo, Sara; Facchetti, Fabio; Pileri, Stefano; et al.
Abstract Background The oncogenic transcription factorMYC is pathologically activated in many human malignancies. A paradigm forMYC dysregulation is offered by Burkitt lymphoma, where chromosomal translocations leading to Immunoglobulin gene-MYC fusion are the crucial initiating oncogenic events. However, Burkitt lymphoma cases with no detectableMYC rearrangement but maintaining MYC expression have been identified and alternative mechanisms can be involved inMYC dysregulation in these cases. Methods We studied the microRNA profile ofMYC translocation-positive andMYC translocation-negative Burkitt lymphoma cases in order to uncover possible differences at the molecular level. Data was validated at the mRNA and protein level by quantitative Real-Time polymerase chain reaction and immunohistochemistry, respectively. Results We identified four microRNAs differentially expressed between the two groups. The impact of these microRNAs on the expression of selected genes was then investigated. Interestingly, inMYC translocation-negative cases we found over-expression of DNA-methyl transferase family members, consistent to hypo-expression of the hsa-miR-29 family. This finding suggests an alternative way for the activation of lymphomagenesis in these cases, based on global changes in methylation landscape, aberrant DNA hypermethylation, lack of epigenetic control on transcription of targeted genes, and increase of genomic instability. In addition, we observed an over-expression of anotherMYC family gene member, MYCN that may therefore represent a cooperating mechanism of MYC in driving the malignant transformation in those cases lacking an identifiableMYC translocation but expressing the gene at the mRNA and protein levels. Conclusions Collectively, our results showed thatMYC translocation-positive andMYC translocation-negative Burkitt lymphoma cases are slightly different in terms of microRNA and gene expression.MYC translocation-negative Burkitt lymphoma, similarly to other aggressive B-cell non Hodgkin's lymphomas, may represent a model to understand the intricate molecular pathway responsible forMYC dysregulation in cancer.